For Debate: The Significance of Etiologic Diagnosis in Neonates with Overgrowth Syndromes. Lesson Learned from the Simpson-Golabi-Behmel Syndrome - Plachý, Lukáš; Elblová, Lenka; Neuman, Vít; Fencl, Filip; Bláhová, Květa; Straňák, Zbyněk; Lebl, Jan; Průhová, Štěpánka (Pediatric endocrinology reviews, 2018)
Overgrowth syndromes are rare genetic disorders characterized by excessive pre- and postnatal growth accompanied by dysmorphic features and developmental disorders. In addition to other health hazards, the life expectancy of affected children may be compromised due to an increased risk of developing tumors. To demonstrate the need for early recognition, correct diagnostic evaluation and adequate follow-up, we present a family with recurrent Simpson-Golabi-Behmel syndrome (SGBS). SGBS is a X-linked neonatal overgrowth syndrome caused by mutations in the GPC3 or GPC4 genes. All three affected males manifested with congenital diaphragmatic hernia. When fetal overgrowth and congenital diaphragmatic hernia co-occur, the choice for a possible cause is limited among SGBS, Marfan syndrome and Pallister-Killian syndrome. Their different phenotypes allow clinical assessment and correct diagnosis in most cases and should be followed by genetic testing. Regular oncologic screening aimed towards early recognition of malignant tumors may improve long-term outcomes in SGBS as well as in all other overgrowth syndromes.
Keywords: Genetic Diseases, X-Linked; srdeční arytmie; Intellectual Disability; Gigantism; mužské pohlaví; mentální retardace; vrozené srdeční vady; Arrhythmias, Cardiac; Overgrowth syndromes; Simpson-Golabi-Behmel syndrome; Infant, Newborn; novorozenec; gigantismus; Humans; GPC3; Glypicans; glypikany; Heart Defects, Congenital; Congenital diaphragmatic hernia; Hepatoblastoma; genetické nemoci vázané na chromozom X; lidé; Male